A framework for designing patient‐specific bioprosthetic heart valves using immersogeometric fluid–structure interaction analysis. (25th January 2018) - Xu, Fei; Morganti, Simone; Zakerzadeh, Rana; Kamensky, David; Auricchio, Ferdinando; Reali, Alessandro; Hughes, Thomas J. R.; Sacks, Michael S.; Hsu, Ming‐Chen
Abstract: Numerous studies have suggested that medical image derived computational mechanics models could be developed to reduce mortality and morbidity due to cardiovascular diseases by allowing for patient‐specific surgical planning and customized medical device design. In this work, we present a novel framework for designing prosthetic heart valves using a parametric design platform and immersogeometric fluid–structure interaction (FSI) analysis. We parameterize the leaflet geometry using several key design parameters. This allows for generating various perturbations of the leaflet design for the patient‐specific aortic root reconstructed from the medical image data. Each design is analyzed using our hybrid arbitrary Lagrangian–Eulerian/immersogeometric FSI methodology, which allows us to efficiently simulate the coupling of the deforming aortic root, the parametrically designed prosthetic valves, and the surrounding blood flow under physiological conditions. A parametric study is performed to investigate the influence of the geometry on heart valve performance, indicated by the effective orifice area and the coaptation area. Finally, the FSI simulation result of a design that balances effective orifice area and coaptation area reasonably well is compared with patient‐specific phase contrast magnetic resonance imaging data to demonstrate the qualitative similarity of the flow patterns in the ascending aorta. Abstract : In this work, we present a framework for designing patient‐specific prosthetic heart valves using parametric design and immersogeometric fluid–structure interaction (FSI) analysis. Leaflet geometry is generated from several design parameters, while conforming to a medical image derived aortic root geometry at the attached edge. Each design is analyzed using our immersogeometric FSI methodology. A parametric study investigates the influence of geometry on valve performance. Simulation results are compared with phase contrast magnetic resonance imaging data.